The impact of stratospheric resolution on the detectability of climate change signals in the free atmosphere. Issue 5 (6th March 2013) - Mitchell, D. M.; Stott, P. A.; Gray, L. J.; Allen, M. R.; Lott, F. C.; Butchart, N.; Hardiman, S. C.; Osprey, S. M.
Abstract [1] We perform a comparison of temperature changes in the free atmosphere over the period 1961–2010 using a high‐top (lid at 84 km) and low‐top (lid at 40 km) version of the HadGEM2 atmosphere‐ocean global climate model. Model simulations of historical climate change that include key anthropogenic and natural external forcings are compared with three different radiosonde data sets. We also apply a regression‐based "optimal fingerprinting" method to determine whether model‐predicted temperature‐change signals in response to external forcing are identifiable in observations. This method employs simulations that isolate the signals associated with different sets of external forcings (well‐mixed GHGs and natural external factors). In both high‐ and low‐top models, we obtain positive detection of the signals arising from anthropogenic influences. We find statistically significant differences between the latitude‐height temperature signals simulated by the high‐ and low‐top models, particularly in the tropical lower stratosphere. The scaling factors associated with each of the separate forcings are more tightly constrained in the high‐top over the low‐top model, but otherwise are similar in nature. Finally, we show that in detecting the GHG fingerprint, it is the entire vertical temperature profile that is important, not simply the lower‐most tropospheric levels.